Not the Prophet like Moses, but the One of Whom the Prophets Spoke: Deut 18:15, 18–19 in Acts 3:22 and 7:37 - Akagi, Kai (Novum Testamentum, 2022)
The dominant interpretation of Acts 3:22 and 7:37 understands Deut 18:15, 18–19 to be applied to Jesus so as to identify him as an anticipated, individual “prophet like Moses.” Interpreting these verses instead as understanding Deut 18 as a general reference to prophets, however, provides a smoother reading that aligns with the Lukan theme of the prophetic anticipation of Jesus as the messiah. Other literature does not provide decisive support that Deut 18 would be interpreted as prophesying an individual. Jesus is not the prophet like Moses, but rather the one of whom Moses and the prophets spoke.